1986
DOI: 10.1152/ajpregu.1986.251.4.r742
|View full text |Cite
|
Sign up to set email alerts
|

Hypotension induced by passive head-up tilt: endocrine and circulatory mechanisms

Abstract: Circulatory changes and arterial plasma hormone concentrations were measured in seven healthy young adults during 30 and 60 degrees passive head-up tilt with the subjects supported by a saddle. The 30 degrees tilt induced a decrease in pulse pressure (Pp) from 45 +/- 2 to 35 +/- 4 (mean +/- SE) mmHg concomitant with an increase in heart rate (HR) from 58 +/- 4 to 78 +/- 8 beats/min and a marginal increase in mean arterial pressure (MAP). Norepinephrine increased from 180 +/- 20 to 310 +/- 40 pg/ml, aldosterone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
111
2

Year Published

1992
1992
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(121 citation statements)
references
References 0 publications
8
111
2
Order By: Relevance
“…3 In addition, it has been observed that the administration of exogenous catecholamines 4 or nitroglycerin 5 before a tilt test promotes neurogenic fainting in susceptible subjects by eliciting a direct or reflex increase in sympathetic activity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…3 In addition, it has been observed that the administration of exogenous catecholamines 4 or nitroglycerin 5 before a tilt test promotes neurogenic fainting in susceptible subjects by eliciting a direct or reflex increase in sympathetic activity.…”
mentioning
confidence: 99%
“…For instance, plasma norepinephrine concentrations have been found to be elevated 3,6 or diminished 7,8 before syncope. Studies based on conventional power spectral analysis of RR variability have indicated increased, 9,10 reduced, 11,12 or unchanged 13 values of the markers of cardiac sympathetic modulation before a vasovagal event.…”
mentioning
confidence: 99%
“…The main receptors involved in these adjustments are the cardiopulmonary mechanoreceptors, located at the level of the right atrium and the pulmonary veins, and the sinoaortic receptors, located in the carotid sinus and aortic arch 38 . In addition to responding, in an isolated form, for the alterations in circulatory volume, these baroreceptors present a complex inhibitory interaction between the cardiopulmonary and the sinoaortic barorefl exes, which causes the reduction in the cardiopulmonary afferent input to increase the gain of sinoaortic barorefl ex 39 .…”
Section: The Orthostatic Posturementioning
confidence: 99%
“…From a functional point of view, the two components of the arterial barorefl ex (carotid and aortic) are not equivalent. It has been suggested that the aortic barorefl ex has a higher threshold and lower sensitivity than the carotid one 38 . The information of the baroreceptors is transmitted through several pathways that accompany the route of the ninth and tenth cranial pairs until the brainstem centers.…”
Section: The Orthostatic Posturementioning
confidence: 99%
“…Examples of these include markedly elevated epinephrine, vasopressin, ␤-endorphins, and pancreatic polypeptide levels and altered baroreceptor sensitivity in the faint-prone individual. 50,51 Such differences (among many others of which we are as yet unaware) may impact the capability of the central nervous system to protect circulatory stability. In this regard, ␤-endorphin levels are increased in both vasovagal syncope and the analogous second stage of hemorrhagic shock.…”
Section: Potential Novel Pharmacological Approachesmentioning
confidence: 99%